PENGEMBANGAN BUKU AJAR APLIKASI MATEMATIKA MENGGUNAKAN PENDEKATAN REACT - Alfiani Athma Putri Rosyadi (Universitas Islam Malang, 2019)
Existing learning equipped with textbooks is expected to convey the concepts contained in the material. Textbooks are prepared using the REACT approach (Relating, Experiencing, Applying, Cooperating and Transferring). The REACT approach was chosen because the facts that appeared in the field of textbooks that had been compiled had not yet linked daily activities, involved student activities and compiled project tasks. Development of textbooks with Mathematics Applications with REACT approach through stages: a) preliminary analysis, b) preparation of textbooks, c) validation and revision, and d) producing textbook products. In the preliminary analysis process there is a process of reviewing the curriculum and related material, then a textbook is prepared which includes: Learning Objectives, Materials, Learning Activities, Evaluation Tools and completeness of textbooks. Next is the stage of validation and revision, in which there is a validation process by experts and improvement of textbooks according to the results of validation. The final step is the textbook product that has been revised and is ready to be printed. Suggestions for the next researcher are the need to add questions and be equipped with answers related to the contents in the textbook. In addition, it can also be added to the addition of studies on supporting research in each chapter to add student references.